What to do when things go wrong : a five-step guide to planning for and surviving the inevitable : and coming out ahead - Supovitz, Frank (New York : McGraw-Hill Education, 2019)
'Manage every business problem like you were born for it -- from a problem customer to a career-threatening crisis It's not being negative or pessimistic to assume that something will always go wrong in business and in your career. It's being realistic. What you do when crisis hits is the only thing matters -- and this proven guide delivers everything you need to take positive action with confidence, skill, and professionalism. In What to Do When Things Go Wrong, Frank Supovitz, the man who has been behind-the-scenes at major events like the Super Bowl, Stanley Cup, and Indy 500 guides you through the process of making sure you handle inevitable problems as if it's something you do day in and day out. Whether you're revealing a new strategy to your team, presenting last year's numbers to the C-suite, or opening your own business, What to Do When Things Go Wrong helps you think through and prepare for all potential problems. You'll learn why things go wrong, how to best go about preventing crisis, and how to fix them when they happen anyway. Complete with stories from the author's clients, executives, entrepreneurs, and others, What to Do When Things Go Wrong is your playbook for ensuring the results you deliver reflect the smart, hard-working professional you are'--
'From the man who made the Super Bowl go off without a hitch - almost - proven five-step program to prepare for and manage any crisis situation with skill and confidence'--
Keywords: Crisis management; Problem solving